INFLUENCE OF PHOTOACTIVATED ROSE BENGAL ON MICROCIRCULATION - T. G. Gryshachova; I. A. Mikhailova; A. V. Struy; S. G. Chephu; N. N. Petrishchev (Biomedical Photonics, 2017)
The study of mean blood velocity changes in rat mesenteric venules (15–30 µm) due to photoactivation (λ = 532 nm, 0,175 W/cm2, 300 s) of i.v. injected Rose Bengal (17 mg/kg) is represented in the article. Using in vivo biomicroscopy the progressive decrease of mean blood velocity both during the laser irradiation and after it was registered. The calculation of thermal effects in the irradiated part of microvessel due to laser absorption by hemoglobin and Rose Bengal showed the rise of temperature was not exceed 0.2оC as compared to initial level. Thus, thermal effect has nearly no significant influence on microvascular disturbances caused by Rose Bengal photoactivation.